High-strength wear-resistant anti-snagging functional dry knitted fabric for exercise training and production process
By combining polyester fiber, aramid fiber, jasper fiber and polyamide fiber with impregnation liquid and modified polyester filament, the problems of abrasion resistance, mechanical strength and moisture absorption and dryness of knitted fabrics have been solved, and a production process for high-strength, anti-snagging sports training knitted fabrics has been realized.
Patent Information
- Application Number
- CN202511905340.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-17
- Publication Date
- 2026-01-16
- Estimated Expiration
- 2045-12-17
AI Technical Summary
Existing knitted fabrics have poor abrasion resistance and mechanical strength, poor snagging resistance, and insufficient moisture absorption, dryness, and washability, which limits their efficiency.
Polyester fiber, aramid fiber, jasper fiber and polyamide fiber are blended into a mixed roving. Through the combination of impregnation liquid and modified polyester filament, the abrasion resistance, mechanical strength and moisture absorption and dryness of the fabric are improved by utilizing the synergistic effect of aluminum borate whiskers, aluminum nitride liquid, β-cyclodextrin-sodium alginate liquid and modified additives.
It significantly improves the abrasion resistance, mechanical strength, snagging resistance and washability of knitted fabrics, enhances the overall coordination and performance stability of the fabric, and maintains excellent performance even after multiple washes.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of knitted fabric, in particular to a high-strength wear-resistant anti-hooking functional dry sports training knitted fabric and a production process. BACKGROUND
[0002] With the rise of the nationwide fitness craze, the demand for sports training clothing continues to grow, and consumers' performance requirements for sports fabric are increasingly demanding. Knitted fabric is a fabric formed by bending yarn into loops and interlocking each other with knitting needles. The difference between knitted fabric and woven fabric is the form of yarn in the fabric. Knitting is divided into weft knitting and warp knitting. Knitted fabric is widely used in garment fabric and lining, home textiles and other products, and is loved by consumers.
[0003] The existing knitted fabric has poor wear resistance, mechanical strength performance, and poor hooking effect, which limits the use efficiency of the product. In addition, the moisture absorption, dryness and wash resistance of the knitted fabric are poor, which further affects the use efficiency of the product. Based on this, the present application provides a high-strength wear-resistant anti-hooking functional dry sports training knitted fabric and a production process. SUMMARY
[0004] In view of the defects of the prior art, the purpose of the present application is to provide a high-strength wear-resistant anti-hooking functional dry sports training knitted fabric and a production process to solve the problems raised in the background art.
[0005] The technical problem solved by the present application adopts the following technical solution: The present application provides a production process for a high-strength wear-resistant anti-hooking functional dry sports training knitted fabric, comprising the following steps: S1, according to the weight part, the raw material is weighed: 30-40 parts of polyester fiber, 20-30 parts of aramid fiber, 5-10 parts of jade fiber and 5-10 parts of polyamide fiber; S2, the polyester fiber, aramid fiber, jade fiber and polyamide fiber are relaxed, then the drawing process is carried out, and the mixed roving is obtained; then 25-30 parts by weight of the mixed roving is immersed in 100-110 parts by weight of the soaking liquid for soaking improvement, after soaking, drying is carried out, and the soaked mixed roving body is obtained; S3, the soaked mixed roving body and modified polyester filament are woven by a circular knitting machine according to a weight ratio of 1:1, after weaving, heat setting treatment is finally carried out, the setting temperature is 165-170 DEG C, the setting speed is 20-25 m / min, and the setting width is 150-160 cm, so that the sports training knitted fabric is obtained.
[0006] Preferably, the relaxation treatment temperature is 65-70 DEG C, and the time is 35-45 min; The infiltration temperature is 60-65℃, the infiltration pressure is 40-50MPa, and the infiltration time is 1-2h. The drawing process is divided into three passes, the first pass is 12-14mm, the second pass is 10-12mm, and the third pass is 8-10mm, and the drawing speed is 280-300m / min.
[0007] Preferably, the preparation method of the infiltration solution is: S01: 10-15 parts by weight of aluminum borate whiskers are stirred in 140-150 parts by weight of potassium permanganate solution, then washed with water, filtered, and dried, and the dried aluminum borate whiskers are ultrasonically treated in an aluminum nitride solution 5-8 times the total amount of the dried aluminum borate whiskers, after treatment, filtered, and dried to obtain an aluminum nitride-whisker loaded agent; S02: Preparation of β-cyclodextrin-sodium alginate solution: S02a: 3-5 parts of β-cyclodextrin and 1-2 parts of silane coupling agent KH550 are added to 10-15 parts of 75-85% ethanol solution and stirred uniformly to obtain a β-cyclodextrin agent; S02b: 5-8 parts of sodium alginate powder, 4-7 parts of montmorillonite, and 3-5 parts of boron oxide are added to 5-8 parts of 8% sodium silicate solution and stirred thoroughly to obtain a sodium alginate composite solution; The sodium alginate composite solution and the β-cyclodextrin agent are mixed and ball milled at a weight ratio of (5-7):11, the ball milling speed is 700-800r / min, and the ball milling time is 2h, after ball milling, a β-cyclodextrin-sodium alginate solution is obtained; S03: The β-cyclodextrin-sodium alginate solution and the nano-aluminum oxide-whisker loaded agent are further ball milled at a weight ratio of (8-11):5, the ball milling speed is 1200-1500r / min, and the ball milling time is 1h, after ball milling, an infiltration solution is obtained.
[0008] Preferably, the mass fraction of the potassium permanganate solution in S01 is 5-8%, and the ultrasonic power in S01 is 350-400W, and the ultrasonic treatment time is 2h.
[0009] Preferably, the preparation method of the aluminum nitride solution is: The diatomite, carbon nanotubes, and sodium dodecyl benzene sulfonate solution are uniformly blended at a weight ratio of (4-6):(2-3):15 to obtain a diatomite solution, and then 4-6 parts of aluminum nitride and 2-5 parts of graphene are added to 8-12 parts of the diatomite solution and stirred to obtain an aluminum nitride solution.
[0010] Preferably, the mass fraction of the sodium dodecyl benzene sulfonate solution is 10-15%.
[0011] Preferably, the stirring speed of the stirring treatment is 450-550 r / min, the stirring time is 2 h, and the stirring temperature is 55-65 DEG C.
[0012] Preferably, the preparation method of the modified polyester filament is: S11: 3-5 parts of basalt fiber, 2-4 parts of silicon dioxide, 3-5 parts of silane coupling agent KH560 and 10-15 parts of sodium citrate solution and 3-5 parts of kaolin are fully blended, then filtered, dried, and the modified additive is obtained; S12: 80-90 parts of polyester resin, 5-10 parts of modified additive are blended and extruded, the extrusion temperature is 295-300 DEG C, the extrusion pressure is 10 MPa, the extrusion is finished, the polyester master batch is obtained, the polyester master batch and the toughening agent of epoxy cyclohexane base polyether polyol are mixed according to the weight ratio (7-8):1, and then melt spinning treatment is carried out, so that the modified polyester filament is obtained.
[0013] Preferably, the spinning speed of the melt spinning is 3000-3500 m / min.
[0014] Preferably, the mass fraction of the sodium citrate solution is 10-15%.
[0015] The application also provides a production process of the functional dry and comfortable sports training knitted fabric with high strength, wear resistance and anti-hooking function.
[0016] Compared with the prior art, the application has the following beneficial effects: The knitted fabric for sports training of the present application is prepared by blending polyester fiber, aramid fiber, jade fiber and polyamide fiber, and then the blended roving is improved by soaking in a soaking liquid, and finally modified polyester filament is used for circular knitting improvement. Through the mutual cooperation and synergistic effect of the raw materials, the obtained knitted fabric has excellent wear resistance, mechanical strength performance, hooking resistance effect, and the moisture absorption and dryness of the knitted fabric and the washing resistance effect are remarkable, and the comprehensive coordination of the product is excellent. The soaking liquid uses aluminum borate whiskers as the matrix, and the aluminum borate whiskers have a whisker skeleton, which plays a system support effect. After treatment with potassium permanganate solution, the activity of the aluminum borate whiskers is optimized, and then aluminum nitride liquid is used for coordination and optimization. The aluminum nitride liquid uses aluminum nitride as the matrix, and the blending and coordination of diatomite, carbon nanotubes and graphene are used in combination with the aluminum borate whisker system, so that the performance coordination of the product is further improved. Diatomite has a porous structure and can be used as a carrier to adsorb aluminum nitride, graphene and other nanoparticles, while improving the dispersibility of the loaded agent to avoid particle agglomeration. Both carbon nanotubes and graphene are high-strength nanomaterials. Carbon nanotubes can form a tubular support, and graphene provides sheet-shaped reinforcement to synergistically improve the overall mechanical properties of the loaded agent. Graphene has excellent thermal conductivity and can assist in evaporation of sweat, while maintaining dryness. Through the blending and coordination of the raw materials, the comprehensive effect of the product is further improved. The hollow structure of β-cyclodextrin in the β-cyclodextrin-sodium alginate liquid can be combined with the montmorillonite, boron oxide and other systems to enhance the structural stability of the system. The cavity structure of β-cyclodextrin can adsorb sweat, and then the graphene, aluminum borate whisker and other systems can quickly guide the sweat out, and the structure formed by the β-cyclodextrin-sodium alginate liquid fills the gaps between the fibers, making the fabric structure dense and further enhancing the system performance of the product. In the preparation of modified polyester filament, modified additives are added for blending and extrusion. Basalt fiber in the modified additives enhances the system performance, and silica and kaolin have reinforcing effect. Through the cooperation and coordination of the raw materials, the performance of the system is further improved, and the performance of the product is further improved. DETAILED DESCRIPTION
[0017] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application.
[0018] The production process of the high-strength wear-resistant anti-hooking functional dry sports training knitted fabric of the present embodiment includes the following steps: S1, the raw materials are weighed according to the weight parts: 30-40 parts of polyester fiber, 20-30 parts of aramid fiber, 5-10 parts of jade fiber and 5-10 parts of polyamide fiber; S2, the polyester fiber, aramid fiber, jade fiber and polyamide fiber are relaxed, and then a drawing process is performed to obtain a mixed roving; 25-30 parts by weight of the mixed roving are immersed in 100-110 parts by weight of the impregnating solution for impregnation improvement, and after the immersion is completed, drying is performed to obtain an impregnated mixed roving body; S3, the impregnated mixed roving body and the modified polyester filament are knitted by using a circular knitting machine at a weight ratio of 1:1, and finally heat setting is performed at a setting temperature of 165-170℃, a setting speed of 20-25 m / min and a setting width of 150-160 cm to obtain the sports training knitted fabric.
[0019] Preferably, the treatment temperature of the relaxation treatment is 65-70℃, and the treatment time is 35-45 min; The impregnation temperature of the impregnation improvement is 60-65℃, the impregnation pressure is 40-50 MPa, and the impregnation time is 1-2 h; The drawing process is divided into three passes, the first pass has a roller gauge of 12-14 mm, the second pass has a roller gauge of 10-12 mm, and the third pass has a roller gauge of 8-10 mm, and the drawing speed is 280-300 m / min.
[0020] The preparation method of the impregnating solution of the embodiment is as follows: S01: 10-15 parts by weight of aluminum borate whiskers are fully stirred in 140-150 parts by weight of a potassium permanganate solution, and then washed with water, filtered, and dried; the dried aluminum borate whiskers are ultrasonically treated in an aluminum nitride solution in an amount of 5-8 times the total amount of the dried aluminum borate whiskers, and after the treatment is completed, the mixture is filtered and dried to obtain an aluminum nitride-whisker supported agent; S02: Preparation of a β-cyclodextrin-sodium alginate solution: S02a: 3-5 parts of β-cyclodextrin and 1-2 parts of silane coupling agent KH550 are added to 10-15 parts of an ethanol solution with a mass fraction of 75-85%, and stirred uniformly to obtain a β-cyclodextrin agent; S02b: 5-8 parts of sodium alginate powder, 4-7 parts of montmorillonite, and 3-5 parts of boron oxide are added to 5-8 parts of a sodium silicate solution with a mass fraction of 8%, and stirred fully to obtain a sodium alginate composite solution; The sodium alginate composite solution and the β-cyclodextrin agent are mixed at a weight ratio of (5-7):11, ball milled at a speed of 700-800 r / min for 2 h, and after the ball milling is completed, a β-cyclodextrin-sodium alginate solution is obtained; S03: The β-cyclodextrin-sodium alginate solution and the nano-aluminum oxide-whisker supported agent are further ball milled at a weight ratio of (8-11):5, a speed of 1200-1500 r / min for 1 h, and after the ball milling is completed, an impregnating solution is obtained.
[0021] The mass fraction of the potassium permanganate solution in S01 of the embodiment is 5-8%; the ultrasonic power of the ultrasonic treatment in S01 is 350-400W, and the ultrasonic treatment lasts for 2h.
[0022] The preparation method of the aluminum nitride liquid of the embodiment is as follows: The diatomite, carbon nanotubes and sodium dodecyl benzene sulfonate solution are uniformly blended according to the weight ratio (4-6):(2-3):15 to obtain a diatomite liquid; then 4-6 parts of aluminum nitride and 2-5 parts of graphene are added to 8-12 parts of the diatomite liquid for stirring treatment, and after the stirring treatment, the aluminum nitride liquid is obtained.
[0023] The mass fraction of the sodium dodecyl benzene sulfonate solution of the embodiment is 10-15%.
[0024] The stirring speed of the stirring treatment of the embodiment is 450-550r / min, the stirring treatment lasts for 2h, and the stirring temperature is 55-65℃.
[0025] The preparation method of the modified polyester filament of the embodiment is as follows: S11: 3-5 parts of basalt fiber, 2-4 parts of silicon dioxide, 3-5 parts of silane coupling agent KH560, 10-15 parts of sodium citrate solution and 3-5 parts of kaolin are uniformly blended, and then are extracted, filtered and dried to obtain a modified additive; S12: 80-90 parts of polyester resin and 5-10 parts of the modified additive are blended and extruded, the extrusion temperature is 295-300℃, the extrusion pressure is 10MPa, after the extrusion, a polyester master batch is obtained, the polyester master batch and a toughening agent of epoxy cyclohexane-based polyether polyol are mixed according to the weight ratio (7-8):1, and then are subjected to melt spinning treatment, so that the modified polyester filament is obtained.
[0026] The spinning speed of the melt spinning of the embodiment is 3000-3500m / min.
[0027] The mass fraction of the sodium citrate solution of the embodiment is 10-15%.
[0028] The production process of the high-strength wear-resistant anti-hooking functional dry and cool sports training knitted fabric of the embodiment produces a knitted fabric. Embodiment 1
[0029] The production process of the high-strength wear-resistant anti-hooking functional dry and cool sports training knitted fabric of the embodiment includes the following steps: S1, the raw materials are weighed according to the weight parts: 30 parts of polyester fiber, 20 parts of aramid fiber, 5 parts of jade fiber and 5 parts of polyamide fiber; S2, the polyester fiber, aramid fiber, jade fiber and polyamide fiber are relaxed, then the blending process is performed to obtain a blended roving; then 25 parts by weight of the blended roving is immersed in 100 parts by weight of the infiltration solution for infiltration improvement, after the infiltration is completed, drying is performed to obtain an infiltrated blended roving body; S3, the infiltrated blended roving body and the modified polyester filament are knitted by using a circular knitting machine at a weight ratio of 1:1, after the knitting is completed, heat setting is performed at a setting temperature of 165℃, a setting speed of 20 m / min and a setting width of 150 cm, thereby obtaining the sports training knitted fabric.
[0030] The treatment temperature of the relaxation treatment is 65℃, and the treatment time is 35 min; The infiltration temperature of the infiltration improvement is 60℃, the infiltration pressure is 40 MPa, and the infiltration time is 1 h; The blending process is divided into three passes, the first pass has a roller gauge of 12 mm, the second pass has a roller gauge of 10 mm, and the third pass has a roller gauge of 8 mm, and the blending speed is 280 m / min.
[0031] The preparation method of the infiltration solution of the embodiment is as follows: S01: 10 parts by weight of aluminum borate whiskers are first stirred in 140 parts by weight of a potassium permanganate solution, then washed with water, filtered, and dried, the dried aluminum borate whiskers are ultrasonically treated in an aluminum nitride solution at 5-8 times the total amount of the dried aluminum borate whiskers, after the treatment is completed, the product is filtered and dried to obtain an aluminum nitride-whisker supported agent; S02: Preparation of a β-cyclodextrin-sodium alginate solution: S02a: 3 parts of β-cyclodextrin and 1 part of silane coupling agent KH550 are added to 10 parts of an ethanol solution with a mass fraction of 75% and stirred uniformly to obtain a β-cyclodextrin agent; S02b: 5 parts of sodium alginate powder, 4 parts of montmorillonite, and 3 parts of boron oxide are added to 5 parts of a sodium silicate solution with a mass fraction of 8%, and stirred uniformly to obtain a sodium alginate composite solution; The sodium alginate composite solution and the β-cyclodextrin agent are mixed uniformly at a weight ratio of 5:11 and subjected to ball milling at a rotation speed of 700 r / min for 2 h, and after the ball milling is completed, a β-cyclodextrin-sodium alginate solution is obtained; S03: The β-cyclodextrin-sodium alginate solution and the nano-aluminum oxide-whisker supported agent are further subjected to ball milling at a weight ratio of 8:5, a rotation speed of 1200 r / min, and for 1 h, and after the ball milling is completed, an infiltration solution is obtained.
[0032] The mass fraction of the potassium permanganate solution in S01 of the embodiment is 5%; the ultrasonic power for the ultrasonic treatment in S01 is 350 W, and the ultrasonic treatment is performed for 2 h.
[0033] The preparation method of the aluminum nitride solution of the embodiment is as follows: The diatomite, carbon nanotubes and sodium dodecyl benzene sulfonate solution are uniformly blended according to the weight ratio of 4:2:15 to obtain a diatomite solution; then 4 parts of aluminum nitride and 2 parts of graphene are added into 8 parts of the diatomite solution for stirring treatment, and after the stirring is completed, an aluminum nitride solution is obtained.
[0034] The mass fraction of the sodium dodecyl benzene sulfonate solution in this embodiment is 10%.
[0035] The stirring speed of the stirring treatment in this embodiment is 450 r / min, the stirring time is 2 h, and the stirring temperature is 55℃.
[0036] The preparation method of the modified polyester filament in this embodiment is as follows: S11: 3 parts of basalt fiber, 2 parts of silicon dioxide, 3 parts of silane coupling agent KH560 and 10 parts of sodium citrate solution, and 3 parts of kaolin are fully blended, and then are subjected to suction filtration and drying to obtain a modified additive; S12: 80 parts of polyester resin and 5 parts of the modified additive are blended and extruded, the extrusion temperature is 295℃, the extrusion pressure is 10 MPa, and after the extrusion is completed, a polyester master batch is obtained; the polyester master batch and a toughening agent of epoxy cyclohexane-based polyether polyol are mixed according to a weight ratio of 7:1, and then are subjected to melt spinning treatment, so that a modified polyester filament is obtained.
[0037] The spinning speed of the melt spinning in this embodiment is 3000 m / min.
[0038] The mass fraction of the sodium citrate solution in this embodiment is 10%. Embodiment 2
[0039] The production process of the high-strength wear-resistant anti-hooking functional dry sports training knitted fabric in this embodiment includes the following steps: S1, the raw materials are weighed according to the weight parts: 40 parts of polyester fiber, 30 parts of aramid fiber, 10 parts of jade fiber and 10 parts of polyamide fiber; S2, the polyester fiber, aramid fiber, jade fiber and polyamide fiber are subjected to relaxation treatment, and then are subjected to a drawing process to obtain a mixed roving; then 30 parts by weight of the mixed roving is immersed in 110 parts by weight of an impregnating solution for impregnation improvement, after the impregnation is completed, drying is performed to obtain an impregnated mixed roving body; S3, the impregnated mixed roving body and the modified polyester filament are woven by using a circular knitting machine according to a weight ratio of 1:1, after the weaving is completed, a heat setting process is finally performed, the setting temperature is 170℃, the setting speed is 25 m / min, and the setting width is 160 cm, so that a sports training knitted fabric is obtained.
[0040] The relaxation treatment is performed at a temperature of 70℃ for 45 min; The impregnation temperature for the impregnation improvement is 65℃, the impregnation pressure is 50 MPa, and the impregnation time is 2 h; The drawing process is divided into three passes, the first pass is 14mm, the second pass is 12mm, and the third pass is 10mm, and the drawing speed is 300m / min.
[0041] The preparation method of the infiltration liquid of the embodiment is as follows: S01: 15 parts by weight of aluminum borate whiskers are first stirred in 150 parts by weight of potassium permanganate solution, then washed with water, filtered, and dried, and the dried aluminum borate whiskers are ultrasonically treated in an aluminum nitride liquid 8 times the total amount of the dried aluminum borate whiskers, after the treatment, filtered, and dried to obtain an aluminum nitride-whisker loaded agent; S02: Preparation of a beta-cyclodextrin-sodium alginate liquid: S02a: 5 parts of beta-cyclodextrin and 2 parts of silane coupling agent KH550 are added to 15 parts of 85% mass fraction ethanol solution and stirred uniformly to obtain a beta-cyclodextrin agent; S02b: 8 parts of sodium alginate powder, 7 parts of montmorillonite, and 5 parts of boron oxide are added to 8 parts of 8% mass fraction sodium silicate solution and stirred thoroughly to obtain a sodium alginate composite liquid; The sodium alginate composite liquid and the beta-cyclodextrin agent are mixed uniformly at a weight ratio of 7:11 and subjected to ball milling at a rotation speed of 800r / min for 2h, and the beta-cyclodextrin-sodium alginate liquid is obtained after the ball milling. S03: The beta-cyclodextrin-sodium alginate liquid and the nano-aluminum oxide-whisker loaded agent are further subjected to ball milling at a weight ratio of 11:5, a rotation speed of 1500r / min for 1h, and the infiltration liquid is obtained after the ball milling.
[0042] The mass fraction of the potassium permanganate solution in S01 of the embodiment is 8%; the ultrasonic power in S01 is 400W, and the ultrasonic treatment is performed for 2h.
[0043] The preparation method of the aluminum nitride liquid of the embodiment is as follows: The diatomite, carbon nanotubes, and sodium dodecyl benzene sulfonate solution are uniformly blended at a weight ratio of 6:3:15 to obtain a diatomite liquid; and 6 parts of aluminum nitride and 5 parts of graphene are added to 12 parts of the diatomite liquid and stirred to obtain the aluminum nitride liquid.
[0044] The mass fraction of the sodium dodecyl benzene sulfonate solution of the embodiment is 15%.
[0045] The stirring rotation speed of the stirring treatment of the embodiment is 550r / min, the stirring is performed for 2h, and the stirring temperature is 65℃.
[0046] The preparation method of the modified polyester filament of the embodiment is as follows: S11: 5 parts of basalt fiber, 4 parts of silicon dioxide, 5 parts of silane coupling agent KH560 and 15 parts of sodium citrate solution, and 5 parts of kaolin were blended and fully mixed, then filtered and dried to obtain a modified additive; S12: 90 parts of polyester resin and 10 parts of the modified additive were blended and extruded, the extrusion temperature was 300 DEG C, the extrusion pressure was 10 MPa, and after the extrusion was completed, a polyester master batch was obtained, the polyester master batch and a toughening agent of epoxy cyclohexane-based polyether polyol were mixed according to a weight ratio of 8:1, and then melt spinning treatment was performed, so that a modified polyester filament was obtained.
[0047] The spinning speed of the melt spinning in this embodiment was 3500 m / min.
[0048] The mass fraction of the sodium citrate solution in this embodiment was 15%. Embodiment 3
[0049] The production process of the high-strength wear-resistant anti-hooking functional dry sports training knitted fabric in this embodiment includes the following steps: S1, the raw materials were weighed according to the weight parts: 35 parts of polyester fiber, 25 parts of aramid fiber, 7.5 parts of jade fiber and 7.5 parts of polyamide fiber; S2, the polyester fiber, aramid fiber, jade fiber and polyamide fiber were relaxed and treated, and then a drawing process was performed to obtain a mixed roving; then 27.5 parts by weight of the mixed roving was immersed in 105 parts by weight of the impregnating solution for impregnation improvement, after the impregnation was completed, drying was performed to obtain an impregnated mixed roving body; S3, the impregnated mixed roving body and the modified polyester filament were woven by using a circular knitting machine according to a weight ratio of 1:1, after the weaving was completed, a heat setting process was finally performed, the setting temperature was 168 DEG C, the setting speed was 22.5 m / min, and the setting width was 155 cm, so that a sports training knitted fabric was obtained.
[0050] The treatment temperature of the relaxation treatment was 68 DEG C, and the time was 40 min; The impregnation temperature of the impregnation improvement was 62.5 DEG C, the impregnation pressure was 45 MPa, and the impregnation time was 1.5 h; The drawing process was divided into three passes, the first pass had a roller gauge of 13 mm, the second pass had a roller gauge of 11 mm, and the third pass had a roller gauge of 9 mm, and the drawing speed was 290 m / min.
[0051] The preparation method of the impregnating solution in this embodiment was as follows: S01: 12.5 parts by weight of aluminum borate whiskers were first stirred in 145 parts by weight of a potassium permanganate solution, then washed with water, filtered and dried, the dried aluminum borate whiskers were ultrasonically treated in an aluminum nitride solution with a total amount of 6.5 times that of the aluminum borate whiskers, after the treatment was completed, the mixture was filtered and dried to obtain an aluminum nitride-whisker supported agent; S02: Preparation of a beta-cyclodextrin-sodium alginate solution S02a: 4 parts of beta-cyclodextrin, 1.5 parts of silane coupling agent KH550 were added to a 12.5 parts of 80% mass fraction ethanol solution and stirred uniformly to obtain a beta-cyclodextrin agent; S02b: 6.5 parts of sodium alginate powder, 5.5 parts of montmorillonite, 4 parts of boron oxide were added to 6.5 parts of 8% mass fraction sodium silicate solution and stirred fully to obtain a sodium alginate composite solution; The sodium alginate composite solution and the beta-cyclodextrin agent were mixed uniformly at a weight ratio of 6:11 and subjected to ball milling at a rotation speed of 7500 r / min for 2 h, and then a beta-cyclodextrin-sodium alginate solution was obtained. S03: The beta-cyclodextrin-sodium alginate solution and the nano-alumina-whisker supporting agent were further subjected to ball milling at a weight ratio of 9:5, a rotation speed of 1350 r / min for 1 h, and then a soaking solution was obtained.
[0052] The mass fraction of the potassium permanganate solution in S01 of this example was 6.5%; the ultrasonic power in the ultrasonic treatment in S01 was 370 W, and the ultrasonic treatment was performed for 2 h.
[0053] The preparation method of the aluminum nitride solution in this example was as follows: The diatomite, carbon nanotubes and sodium dodecyl benzene sulfonate solution were uniformly blended at a weight ratio of 5:2.5:15 to obtain a diatomite solution; then 5 parts of aluminum nitride and 3.5 parts of graphene were added to 10 parts of the diatomite solution and stirred to obtain an aluminum nitride solution.
[0054] The mass fraction of the sodium dodecyl benzene sulfonate solution in this example was 12.5%.
[0055] The stirring rotation speed in the stirring treatment in this example was 500 r / min, the stirring was performed for 2 h, and the stirring temperature was 60°C.
[0056] The preparation method of the modified polyester filament in this example was as follows: S11: 4 parts of basalt fiber, 3 parts of silicon dioxide, 4 parts of silane coupling agent KH560, 12.5 parts of sodium citrate solution and 4 parts of kaolin were uniformly blended, and then suction filtration and drying were performed to obtain a modified additive; S12: 85 parts of polyester resin and 7.5 parts of the modified additive were blended and extruded at an extrusion temperature of 298°C and an extrusion pressure of 10 MPa to obtain a polyester master batch; the polyester master batch and a toughening agent of epoxy cyclohexane-based polyether polyol were mixed at a weight ratio of 7.5:1, and then melt spinning treatment was performed to obtain a modified polyester filament.
[0057] The spinning speed in the melt spinning in this example was 3250 m / min.
[0058] The mass fraction of the sodium citrate solution of the present embodiment is 12.5%.
[0059] Comparative Example 1: The difference from Example 3 is that no infiltrating liquid is used.
[0060] Comparative Example 2: The difference from Example 3 is that no β-cyclodextrin-sodium alginate liquid is added to the infiltrating liquid.
[0061] Comparative Example 3: The difference from Example 3 is that no β-cyclodextrin agent is added to the β-cyclodextrin-sodium alginate liquid.
[0062] Comparative Example 4: The difference from Example 3 is that no sodium alginate complex liquid is added to the β-cyclodextrin-sodium alginate liquid.
[0063] Comparative Example 5: The difference from Example 3 is that no montmorillonite and boron oxide is added to the sodium alginate complex liquid.
[0064] Comparative Example 6: The difference from Example 3 is that no nano-alumina-whisker loading agent is added to the infiltrating liquid.
[0065] Comparative Example 7: The difference from Example 3 is that no aluminum nitride liquid is added in the preparation of the nano-alumina-whisker loading agent.
[0066] Comparative Example 8: The difference from Example 3 is that no aluminum nitride and graphene is added to the aluminum nitride liquid.
[0067] Comparative Example 9: The difference from Example 3 is that no diatomite and carbon nanotube is added in the preparation of the aluminum nitride liquid.
[0068] Comparative Example 10: The difference from Example 3 is that no modified additive is added in the preparation of the modified polyester filament.
[0069] Comparative Example 11: The difference from Example 3 is that no kaolin is added to the modified additive.
[0070] Comparative Example 12: The difference from Example 3 is that no basalt fiber and silicon dioxide is added to the modified additive.
[0071] The products of Examples 1-3 and Comparative Examples 1-12 are tested for wear resistance, mechanical strength, hooking property under normal conditions, and at the same time, the performance stability of washing resistance (product washing 20 times), and the performance tests of Examples 1-3 and Comparative Examples 1-5 are as follows:
[0072] The performance test of Comparative Examples 6-12 is as follows:
[0073] As can be seen from Comparative Examples 1-12 and Examples 1-3, The wear resistance, breaking strength and looping effect of the product of Example 3 are remarkable, and the product has excellent washing stability.
[0074] Based on the above test, the moisture absorption and dryness are tested, and the performance stability of the washing is also tested. The test method is the same as above. The performance test of Examples 1-3 and Comparative Examples 1-5 is as follows:
[0075] The performance test of Comparative Examples 6-12 is as follows:
[0076] As can be seen from the above performance test, the product of the application has excellent moisture absorption and dryness on the basis of wear resistance, breaking strength and looping, and the product has excellent moisture absorption and dryness stability under washing conditions.
[0077] As can be seen from Comparative Examples 1-12 and Example 3, the performance of the product is deteriorated more obviously without the use of the infiltration liquid, especially under washing conditions, the performance stability of the product is deteriorated more obviously; Without adding the β-cyclodextrin-sodium alginate liquid in the infiltration liquid, without adding the β-cyclodextrin agent in the β-cyclodextrin-sodium alginate liquid, without adding the sodium alginate composite liquid in the β-cyclodextrin-sodium alginate liquid, without adding the montmorillonite and boron oxide in the sodium alginate composite liquid, the performance of the product has a deteriorating trend; At the same time, without adding the nano-alumina-whisker loading agent in the infiltration liquid, without adding the aluminum nitride liquid in the preparation of the nano-alumina-whisker loading agent, without adding the aluminum nitride and graphene in the aluminum nitride liquid, without adding the diatomite and carbon nanotube in the preparation of the aluminum nitride liquid, the performance of the product also has a deteriorating trend to different degrees, especially without adding the nano-alumina-whisker loading agent, the performance of the product is deteriorated more obviously. At the same time, the infiltration liquid prepared by the nano-alumina-whisker loading agent obtained by the specific method of the application and the specific β-cyclodextrin-sodium alginate liquid has the most remarkable performance effect, and the preparation of the aluminum nitride liquid has the specificity. The product has the most remarkable performance effect by using the technical solution of the application.
[0078] The modified polyester filament is prepared without adding a modified additive, kaolin is not added in the modified additive, basalt fiber and silicon dioxide are not added in the modified additive, and the performance of the product has a varying degree of deterioration trend, the modified polyester filament prepared by adding the modified additive of the application has the most excellent performance effect.
[0079] It will be obvious to a person skilled in the art that, without departing from the spirit or essential characteristics of the application, the present application can be implemented in other specific forms thereof. The present embodiments are therefore to be considered in all respects as illustrative and not restrictive, the scope of the application being indicated by the appended claims rather than by the description given above, and all changes which come within the meaning and range of equivalency of the claims are therefore intended to be embraced therein.
[0080] Furthermore, it should be appreciated that although the present specification describes only a few embodiments, additional embodiments of the present application can exist as understood by those skilled in the art upon a complete reading of the description and the claims. The descriptions and examples included herein serve the purpose of enabling those skilled in the art to make and use the application, and not to limit the scope of the application.
Claims
1. A production process of high-strength wear-resistant functional dry sport training knitted fabric with anti-linting function, characterized in that, It comprises the following steps: S1, according to the weight part, the raw material is taken: polyester fiber 30-40 parts, aramid fiber 20-30 parts, 5-10 parts jade fiber and 5-10 parts polyamide fiber; S2, the polyester fiber, aramid fiber, jade fiber and polyamide fiber are relaxed, and then the drawing process is carried out, and the mixed roving is obtained; then 25-30 weight parts of the mixed roving are immersed in 100-110 weight parts of the infiltration liquid for infiltration improvement, after the infiltration is completed, drying is carried out, and the infiltrated mixed roving body is obtained; S3, the infiltrated mixed roving body and modified polyester filament are woven by using a circular knitting machine according to a weight ratio of 1:1, after weaving, finally heat setting treatment is carried out, the setting temperature is 165-170℃, the setting speed is 20-25m / min, and the setting width is 150-160cm, so that the sports training knitted fabric is obtained.
2. The production process of the high-strength wear-resistant anti-hooking functional dry sports training knitted fabric according to claim 1, characterized in that: The treatment temperature of the relaxation treatment is 65-70℃, and the time is 35-45min; The infiltration temperature of the infiltration improvement is 60-65℃, the infiltration pressure is 40-50MPa, and the infiltration time is 1-2h; The drawing process is divided into three passes, the first pass is 12-14mm, the second pass is 10-12mm, and the third pass is 8-10mm, and the drawing speed is 280-300m / min.
3. The process for producing high strength, abrasion resistant, anti-linting functional dry athletic training knitted fabric as claimed in claim 1 wherein, The preparation method of the infiltration liquid is: S01: 10-15 weight parts of aluminum borate whiskers are fully stirred in 140-150 weight parts of potassium permanganate solution, then washed with water, filtered, and dried, the dried aluminum borate whiskers are ultrasonically treated in 5-8 times the total amount of dry aluminum borate whiskers of aluminum nitride liquid, after the treatment is completed, the filtered and dried, and the aluminum nitride-whisker loaded agent is obtained; S02: preparation of β-cyclodextrin-sodium alginate liquid: S02a: 3-5 parts of β-cyclodextrin, 1-2 parts of silane coupling agent KH550 are added to 10-15 parts of 75-85% mass fraction ethanol solution and stirred uniformly to obtain β-cyclodextrin agent; S02b: 5-8 parts of sodium alginate powder, 4-7 parts of montmorillonite, and 3-5 parts of boron oxide are added to 5-8 parts of 8% mass fraction sodium silicate solution and stirred fully to obtain sodium alginate composite liquid; The sodium alginate composite liquid and the β-cyclodextrin agent are mixed uniformly at a weight ratio of (5-7):11, ball milled at a speed of 700-800r / min for 2h, and the β-cyclodextrin-sodium alginate liquid is obtained after ball milling; S03: the β-cyclodextrin-sodium alginate liquid and the nano-aluminum oxide-whisker loaded agent are further ball milled at a weight ratio of (8-11):5, the ball milling speed is 1200-1500r / min, and the ball milling time is 1h, and the infiltration liquid is obtained after ball milling.
4. The process for producing high strength, abrasion resistant, anti-linting functional dry athletic training knitted fabric as claimed in claim 3 wherein, The mass fraction of the potassium permanganate solution in S01 is 5-8%; the ultrasonic power in S01 is 350-400W, and the ultrasonic treatment time is 2h.
5. The production process of the high-strength wear-resistant anti-hooking functional dry sports training knitted fabric according to claim 3, and the preparation method of the aluminum nitride liquid is: The diatomite, carbon nanotube and sodium dodecyl benzene sulfonate solution are blended uniformly according to the weight ratio (4-6):(2-3):15 to obtain a diatomite solution; then 4-6 parts of aluminum nitride and 2-5 parts of graphene are added into 8-12 parts of the diatomite solution for stirring treatment, and the aluminum nitride solution is obtained after the stirring.
6. The production process of the high-strength wear-resistant anti-lint functional dry and comfortable sports training knitted fabric according to claim 5, wherein the mass fraction of the sodium dodecyl benzene sulfonate solution is 10-15%.
7. The production process of the high-strength wear-resistant anti-lint functional dry and comfortable sports training knitted fabric according to claim 5, wherein the stirring speed of the stirring treatment is 450-550 r / min, the stirring time is 2 h, and the stirring temperature is 55-65℃.
8. The production process of the high-strength wear-resistant anti-lint functional dry and comfortable sports training knitted fabric according to claim 1, wherein the preparation method of the modified polyester filament is as follows: S11: 3-5 parts of basalt fiber, 2-4 parts of silicon dioxide, 3-5 parts of silane coupling agent KH560, 10-15 parts of sodium citrate solution and 3-5 parts of kaolin are fully blended, and then are extracted, dried to obtain a modified additive; S12: 80-90 parts of polyester resin and 5-10 parts of the modified additive are blended and extruded, the extrusion temperature is 295-300℃, the extrusion pressure is 10 MPa, and the modified polyester filament is obtained after the extrusion, and the modified polyester filament is mixed with the toughening agent of epoxy cyclohexane-based polyether polyol according to the weight ratio (7-8):1, and then is subjected to melt spinning treatment to obtain the modified polyester filament.
9. The production process of the high-strength wear-resistant anti-lint functional dry and comfortable sports training knitted fabric according to claim 8, wherein the spinning speed of the melt spinning is 3000-3500 m / min, and the mass fraction of the sodium citrate solution is 10-15%.
10. The knitted fabric produced by the production process of the high-strength wear-resistant anti-lint functional dry and comfortable sports training knitted fabric according to any one of claims 1-9.
Citation Information
Patent Citations
Ferric oxide-polyurethane composite emulsion-coated polypropylene-based non-woven sound-absorbing material for automotive interiors
CN104562701A
Preparation method of wear-resistant and anti-cutting UHMWPE (ultra-high molecular weight polyethylene fiber)
CN107326462A
Cool jade anti-ultraviolet functional fabric and preparation method thereof
CN118704154A
Bio-based fabric, clothing and preparation method of bio-based fabric
CN118704156A
Efficient moisture absorption and sweat releasing knitted fabric and preparation method thereof
CN120331022A
Cited By
High-strength polyester fiber with moisture absorption and heating functions and preparation method of high-strength polyester fiber
CN121575504A
Antibacterial cool knitted fabric and application
CN121700588A
Graphene-modified super-soft knitted lyocell fiber product and preparation method thereof
CN122382763A
